A Start-Up Approach to Easy Financing: Solar Energy for Homes and Businesses in Davao City - Co, Zosimo Go (Future Science / FSH-PH Publications, 2024)
This study explores innovative financing solutions to expedite the adoption of solar energy systems among households and businesses in Davao City, Philippines. The urgency of addressing climate change and reducing reliance on non-renewable energy sources has amplified the importance of solar energy as a viable alternative. However, the significant initial investment required for solar installations poses a substantial barrier, especially in developing regions such as the Philippines. Existing literature, including IRENA (2014) and subsequent studies by the International Renewable Energy Agency (2021), underscores both the socio-economic benefits of solar energy and the financial challenges in Southeast Asian adoption, mainly due to high costs. A mixed-methods approach was utilized, integrating quantitative and qualitative research. The quantitative aspect employed a descriptive design, incorporating surveys and interviews with homeowners, business owners, financial institutions, and solar energy providers across three districts in Davao City. The qualitative component involved grounded theory, focusing on in-depth interviews and group discussions to identify barriers and shape tailored solutions. This comprehensive data collection facilitated the development of a locally adapted financing model. Analysis of findings showed that while there is a strong interest in solar energy, significant obstacles persist, including high upfront costs (cited by 68% of respondents) and limited awareness of financing alternatives (noted by 45%). The proposed start-up model incorporates microfinancing and flexible payment structures, addressing these challenges and incorporating community involvement in financing decisions. In conclusion, the study demonstrates that an adaptable financing model can drive solar energy adoption in Davao City, fostering sustainable growth and energy self-sufficiency. This framework could be applied in similar contexts across Southeast Asia, promoting more comprehensive renewable energy access and supporting the region's transition to sustainable energy solutions.